Fluctuations of the initial conditions of the nucleus-nucleus interaction and their influence on the distribution of secondary particles - Fedosimova, A.I. (Recent Contributions to Physics, 2018)
The dynamics of processes nucleus-nucleus interaction is determined not only by the energy and masses of the interacting nuclei, but also by the geometry of the nucleus-nucleus collision. Therefore, investigation of true dynamic correlations of the final states in the interactions of excited hadronic systems is impossible without an analysis of fluctuations of the initial states in individual interactions. The initial state, which is usually very little direct experimental information, leads to significant changes in the distribution of fragments and multiplicity of shower particles. A study of distribution of secondary particles and fragments allows us to give a physical interpretation of the results on the basis of differences in the initial conditions of collisions. A study of the features in the distributions of secondary particles and fragments in collisions of heavy ions with emulsion nuclei, depending on the degree of centrality and the degree of asymmetry of the interacting nuclei, was carried out on the basis of experimental data including the interactions of 197Au 10.7 АGeV with emulsion nuclei Em. Parameters of fragmentation of interacting nuclei for central and peripheral events of different degrees of centrality (periphery) are presented. Parameters of the correlation dependence of the multiplicity of shower particles and the number of fragments of the target nucleus were used as experimental criteria for separating events with dynamic fluctuations, characterizing the features of the interaction process, and events with fluctuations associated with fluctuations in the initial conditions and depending on the degree of centrality (periphery) of the interaction. It is also necessary to take into account the number of multicharged fragments of the projectile nucleus and the distribution of the total charge of the fragments of the incident nucleus, which characterizes the number of interacted protons of the projectile nucleus.